ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN MINAT KUNJUNG ULANG PASIEN RAWAT JALAN DI RSU SEMBIRING DELI TUA - Putri, Rizqi Nanda; Azhary, Muhammad Rifqi; Tampubolon, Elmina; Sitorus, Friska Ernita (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
The intention to revisit is a key component of patient loyalty, which can be strengthened through repeated use of hospital services. One of the primary factors influencing patient satisfaction is service quality. In the context of hospital services, service quality refers to providing healthcare that adheres to quality standards, ensuring that patient and family needs and expectations are met. This leads to greater satisfaction and ultimately enhances trust in the hospital. This study utilized an observational research design with a cross-sectional approach, involving 80 respondents who met the sample readiness criteria at the time of the study. Chi-square analysis was conducted, and the findings revealed that three service quality variables had a significant relationship with outpatient revisit interest at Sembiring Hospital: physical evidence (p = 0.001), reliability (p = 0.001), and responsiveness (p = 0.004). To enhance patient satisfaction and encourage revisit intention, Sembiring Hospital should improve service quality based on patient assessments, particularly in aspects that do not yet meet their expectations. Conducting staff training programs to enhance healthcare professionals’ skills and improve service quality and human resource (HR) performance is also recommended. Additionally, ensuring a comfortable and patient-friendly healthcare environment can make outpatient services more appealing and encourage repeat visits. By implementing these improvements, Sembiring Hospital can increase patient satisfaction, build loyalty, and strengthen trust in its healthcare services.